2014
DOI: 10.15623/ijret.2014.0302024
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Transformation-Based Detection of Masses in Digital Mammograms

Abstract: A Novel Wavelet Transformation-Based Detection of Masses in digital mammograms (WTBDM) is proposed in this paper that enables for the early prognosis of breast cancer. The wavelet analysis is explored for analyzing and identifying strong variations in intensities within the mammographic data which highlights and recognizes the masses effectively. The proposed algorithm, in addition to wavelet transformation, uses morphological preprocessing, region properties and seeded region growing to remove the digitizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Therefore, a new algorithm and set of filters (kernels) is proposed and its results are compared with the Sobel and Laplacian filters for three images. From the results obtained it is found that the proposed algorithm performs better than in terms of less false edges than the Sobel and Laplacian filters ShanmugaVadivu and Sivakumar [28] Wavelet Transformation-Based Detection of…”
Section: -D Spatial Gradiantmentioning
confidence: 98%
“…Therefore, a new algorithm and set of filters (kernels) is proposed and its results are compared with the Sobel and Laplacian filters for three images. From the results obtained it is found that the proposed algorithm performs better than in terms of less false edges than the Sobel and Laplacian filters ShanmugaVadivu and Sivakumar [28] Wavelet Transformation-Based Detection of…”
Section: -D Spatial Gradiantmentioning
confidence: 98%